Case Report: An adult with NCKAP1-related neurodevelopmental disorder and autism spectrum disorder - Jain, Aruna; VanSickle, Elizabeth; Zitano, Lia; Moss, Timothy; Schrader, Erica (Frontiers in Psychiatry, 2025)
IntroductionWe describe a 43-year-old man with neurodevelopmental disorder (NDD) with features of autism spectrum disorder (ASD) due to a rare pathogenic variant in the NCKAP1 gene. There are only 5 young adults described in the literature with NCKAP1-related NDD; there are currently no reports of middle-aged or elderly adults with the condition. The most common clinical characteristics include ASD, intellectual disability (ID), speech-language problems, repetitive behaviors, and seizures.ConclusionThis case report highlights an adult phenotype of NCKAP1-related NDD with goals to 1.) contribute insight into a rare genetic variant leading to NDD with ASD features and 2.) highlight adult manifestations of NCKAP1-related NDD as a patient in middle adulthood with the condition has not yet been reported.